PENGARUH SISTEM PEMBAYARAN NON TUNAI TERHADAP INFLASI di INDONESIA TAHUN 2011-2015 - Ersha Miftakhul Ady (Jurnal Ilmiah Mahasiswa FEB, 2015)
As monetary authorities in Indonesia, Bank Indonesia has the sole task of achieving and maintaining stability of the rupiah,  which one is realized by controlling inflation. On August 14, 2014 Bank Indonesia launched the Gerakan Nasional Non Tunai (GNNT) which aims to introduce and urged the Indonesian people to use non-cash payment system. The movement is in line with Bank Indonesia one of the authorities to regulate and maintain the smooth operation of payment systems that exist in Indonesia. This study aims to see how the effects of non-cash payment system to inflation in Indonesia. This study uses secondary data consisting of Indonesian inflation data, the data nominal amount of credit card transactions, the nominal amount of debit card transactions / ATM, and a nominal amount of e-money transactions obtained from the official website of Bank Indonesia. This study uses multiple regression analysis estimates by using Eviews 6. The results showed that the non-cash payment system that is represented by the nominal amount of credit card transactions, debit card transactions nominal / ATM, and nominal e-money transactions can not affect inflation in Indonesia 2011-2015.Key Words: Non-Cash Payment System ( cashless ) , Inflation , Credit Card , Debit Card / ATM , E -money .